TUJUAN MANAJEMEN PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QURAN - Zaini Dahlan; Afifah Thaiyibah; Mardiana; Taufik Hidayat (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
While management knowledge originated from the West and has spread worldwide, it is important to note that the fundamentals of management have been encapsulated in the Islamic Quran. These principles encompass all aspects of life, including personal and social domains, as well as the broader management of one's life. However, because to the lack of interest among Muslims in deeply studying the contents of the Qur'an as was done during the era of Islamic generosity, knowledge, civilization, and even management experts, are now mostly derived from the Western world.The primary objective of this article is to provide additional understanding to experts in Islamic educational management. This study is a qualitative research investigation conducted using library research. The method used is the thematic method (maudu''i). The data sources consist of primary and secondary data. Primary data includes verses from the Quran and their interpretations, while secondary data consists of relevant journals, books, and articles related to the research topic. The data collection technique involves gathering literature data. The next data analysis technique used is the method of Content Analysis. The objective of Islamic Education management is to effectively and efficiently utilize and manage Islamic educational resources in order to achieve the goals, development, progress, and quality of the process and outcomes of Islamic education. Also, to produce individuals with knowledge, skills, and expertise. Ada dua surah Al-Quran yang menguraikan tujuan manajemen pendidikan menurut para ahli teori manajemen pendidikan dan para mufassir, yaitu Surah Saba (ayat 10-11) dan Surah An-Nahl (ayat 15).